Rev. dr. Edmund Nowicki – Apostolic Administrato r in Gorzów Wielkopolski - Wejman, Grzegorz (Studia Theologica Varsaviensia, 2020)
Rev. PA Edmund Nowicki PhD, a priest of the Archdiocese of Gniezno i Poznań, was strongly associated with Gorzów Wielkopolski through his priestly ministry and with Gdańsk through his episcopal ministry. The work in the apostolic administration in Gorzów Wielkopolski was particularly difficult for him. The enormous area – 1/7 of Poland’s area, the lack of basic religious ministry tools and the difficulties arising from the then authorities posed extremely big problems in creating the pastoral life in the newly created church unit in these lands. More than five years of his work in Western Pomerania and the Lubusz region brought great achievements in the form of a very well-functioning church organization,only permanent church structures were lacking, but nfortunately political factors did not lead to their implementation. This success is the fruit of his fortitude, solid theological and legal background and personal sensitivity. Rev. PA Dr Edmund Nowicki is a great Pole, priest and bishop.